Designing a glycemic control strategy to maintain glucose homeostasis and prevent hypoglycemia for subjects with type 1 diabetes - A. Rafie Lak; O. Vahidi (Iranian Journal of Chemical Engineering)
This paper presents using the fractional PImDn controller module which manipulates insulin infusion rate to maintain normoglycemia in subjects with type 1 diabetes. To prevent severe hypoglycemia, a conventional proportional controller is used to regulate glucagon infusion rate when the blood glucose levels fall below a threshold. Two sets of controller parameters are obtained and evaluated. For the first tuning set, clinical data from an oral glucose tolerance test taken from a group of healthy subjects are used to obtain the controller parameters such that it can mimic a real healthy pancreas. To obtain the second tuning set, the controller parameters are optimized through a sequential quadratic programming algorithm. Using the second tuning set, the in silico 2-hour postprandial test result and comparing it with the glucose concentration trajectory of the healthy subjects show that the controller performs well in returning the blood sugar levels into the glucose homeostasis while keeping the plasma insulin concentration within the acceptable physiological range. It is indicated that the manipulation of glucagon infusion rate is effective in hypoglycemia prevention if more aggressive controller settings are chosen or dysfunctional insulin infusion occurs.